HUMANITARIAN MOVIES: MAKE IT WORK IN SPEAKING CLASS A THEORETICAL BASED GUIDE FOR PRACTICES - Andre Andre; Dimas Dicsa Yudistama; Yulnetri Yulnetri (Universitas Negeri Padang, 2016)
“Leaders in the educator preparation field have a unique opportunity-and a profound obligation-to establish the vision for their programs that will result in a 21th century educator workforce that produces the student outcomes outlined in the Framework for 21th Century Skills Learning.”Hywel, based on his research in University of Leeds, were ELT process undermined student language competence (Kompas: 2011). Furthermore, the goal of 2013 curriculum failed in capturing human character in taught course, particularly, teaching speaking at school. Teaching speaking commonly in boredom processes, further, teacher asked student to talk and perform in front of the class. Moreover, the various ways in teaching speaking has been offered but, it still far from curriculum expectation. Teacher experienced also designated teaching speaking based on 2013 curriculum not maximally as well. The problem is teaching speaking through character still in question. The paper highlight the nature of teaching speaking through humanitarian movies of recount text in developing students character. It means a short humanitarian action in a kind of video to stimulate students in applying character values in daily life. The students are speaking around the cases that found in video as well as character values. It makes the natural approach of humanitarian action in daily life that stimulated students to take an action. After that, the students asked to record their humanitarian action in daily life, especially, they felt directly of their action in mirror life. Finally, student speaks about their record in classroom talk as well as the tremendous moral values based on his/her experience.